Impact of interface traps on switching behavior of normally‐OFF AlGaN/GaN MOS‐HEMTs. Issue 5 (3rd February 2016) - Shi, Yuanyuan; Zhou, Qi; Jin, Yang; Chen, Bowen; Chen, Wanjun; Huang, Wei; Zhang, Bo
Abstract: In this paper, we report an experimental observation of the two‐stage turn‐on characteristic in normally‐OFF Al2 O3 /GaN metal‐oxide‐semiconductor high electron mobility transistors (MOS‐HEMTs) on Si substrate. The impact of oxide/GaN interface traps with different energy levels on the switching behavior of the device was extensively examined by simulation and verified by measurements. The interface traps at 0.4 eV below the bottom of the conduction band ( E it = E C ‐0.4 eV) of GaN buffer with a density of D it = 6.5×10 12 cm ‐2 was identified responsible for the observed two‐stage turn‐on characteristic. The weak Fermi‐level pinning (WFLP) induced by the dynamic electron filling of interface traps may hamper the electron from accumulating in the Al2 O3 /GaN MOS‐channel and then manifests a premature turn‐on during the switching‐on process. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)